The competitive advantage of furniture SMEs in East Java: The role of aggressiveness in entrepreneurship orientation - Ardianus Laurens Paulus; Yustinus Budi Hermanto (Economies, 2022)
This paper analyzes the dimensions of entrepreneurial orientation in Furniture SMEs in East Java, Indonesia, towards competitive advantage. This study uses a quantitative approach with the survey method. This study uses primary data that is self-reported using a self-administered survey by distributing questionnaires directly to 84 owners of small and medium enterprises (SMEs) Furniture in Western East Java, Indonesia. A measurement used the structural equation model (SmartPLS 3.0) to analyze data. Five hypotheses were proposed, and only four had positive significant and positive effects on competitive advantage, that is, the influence of entrepreneurial orientation consisting of proactiveness, innovativeness, aggressiveness, and autonomy. In contrast, the hypothesis related to risk-taking towards the competitive advantage of SMEs Furniture has no positive and significant effect. The findings of this study show that the dominant influence of the entrepreneurial orientation dimension is aggressiveness. The theoretical implication of this research is that furniture business players need to continuously improve their aggressiveness in entrepreneurship according to the theoretical findings in this study, such as introducing innovative products made from local materials and following market trends. This research adds to the theory of aggressiveness in entrepreneurship to encourage innovations that will make industries that use local natural resources more competitively and help government policies. Aggressiveness is required by the furniture business to improve competitiveness for a labor-intensive industry with reliable local content to spur economic growth in Indonesia.
Keywords: 330; aggressiveness; entrepreneurial orientation; furniture; SME